Laporan Kasus Hipokalemi Periodik Paralisis pada Pasien dengan Graves’ Disease - Sirait, Anggi Cahaya Millenia S; Buharman, Borries Foresto; Putri, Adinda Zhafira Dyanti; Putri, Derby Ayudhia Utami Iskandar (Jurnal Penyakit Dalam Indonesia, 2025)
Hypokalemia periodic paralysis (HPP) characterized by episodes of flaccid weakness or paralysis that may be associated with abnormalities of the serum potassium level. HPP often associated with hyperthyroidism and Graves’ disease. HPP prevalence is 1 in 100.000. Each individual has different clinical manifestations, so it’s necessary to adjust therapy based on the etiology. This case report was developed to provide more information regarding Graves’ disease, considering lack of information about management and description of HPP with Graves’ disease. A 27-year-old male with sudden weakness in both legs radiating to upper extremity, shortness of breath, palpitations, and sweating. Over the last 2 months, the patient’s weight has dropped drastically even though his appetite was increased. There were no complaints of nausea, vomiting, or increased frequency of defecation and urination. Previously, the patient had the similar experiences and received potassium transfusion twice. The patients revealed tachycardia, diffuse thyroid gland, fine hand tremor, superior motor streght 222/222 and inferior 111/111, hypokalemia (1.40 mmol/L), T4 total 197.80 nmol/L, and fluorescence T4 >320 m/U/mL. Graves’ disease that has become thyrotoxicosis can be accompanied by a picture of HPP or also called thyrotoxicosis periodic paralysis (TPP). Hypokalemia in TPP are not caused by potassium loss but due to intracellular potassium movement, so there’s a high possibility to hyperkalemia rebound. Treatment of TTP due to Grave’s disease is to prevent potassium transfer by administering beta blocker, potassium replacement, and treating hyperthyroidism.